Perancangan Sistem Absensi Online Untuk Teknisi Harian Berbasis Web View Pada PT. Visionet Data Internasional Menggunakan Metode Extreme Programing - Rofi Pangestu; Heri Haerudin (CV. Multi Kreasi Media, 2023)
Attendance is a routine activity carried out by every employee who works in a company or agency that functions as a record of attendance and affects the value of employee performance. PT. Visionet Data International still uses pen and paper. There are several obstacles that occur in using the procedure, the attendance of these technicians still uses paper and pens, so it is very inconvenient for the technician to be absent from the office first before coming to the client, it causes the technician to be late for about 30 minutes1 hour, because still using paper, technicians' work overtime cannot be controlled so that technicians can write overtime at any time even though they are not working overtime, in the old system, daily technicians did not have daily work reports so technicians could not do any work for a day but still get paid. Therefore we need a web view- based application that can perform attendance and manage overtime in order to run quickly, effectively and efficiently. Made with the extreme programming method, this attendance application is designed to be simple and user friendly. The software used in making this attendance application include PHP, MySQL and Xampp. With this application, it can make it easier for admins and technicians in field work.